2020
DOI: 10.1186/s40168-020-00912-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TMAO productivity from carnitine challenge facilitates personalized nutrition and microbiome signatures discovery

Abstract: The capability of gut microbiota in degrading foods and drugs administered orally can result in diversified efficacies and toxicity interpersonally and cause significant impact on human health. Production of atherogenic trimethylamine N-oxide (TMAO) from carnitine is a gut microbiota-directed pathway and varies widely among individuals. Here, we demonstrated a personalized TMAO formation and carnitine bioavailability from carnitine supplements by differentiating individual TMAO productivities with a recently d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…41,42,43,44 Previously, in a human study, we developed the OCCT, which can robustly distinguish the low-and high-TMAO producers. 37 In this study, high-TMAO producers were de ned as individuals exhibiting OCCT plasma TMAO MAX level ≥ 10 µM 20 . There is currently a lack of studies on the effect of garlic on the gut microbiota in the human body; this study is the rst to demonstrate the impact of garlic on TMAO production by the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…41,42,43,44 Previously, in a human study, we developed the OCCT, which can robustly distinguish the low-and high-TMAO producers. 37 In this study, high-TMAO producers were de ned as individuals exhibiting OCCT plasma TMAO MAX level ≥ 10 µM 20 . There is currently a lack of studies on the effect of garlic on the gut microbiota in the human body; this study is the rst to demonstrate the impact of garlic on TMAO production by the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated that plasma and urine TMAO exhibited a high positive correlation that was consistent with the results from previous studies. 20,37 Currently, the primary genes responsible for converting carnitine to TMA by the gut microbiota remains unclear. A Rieske-type microbial CntA/B enzyme was reported to convert carnitine to TMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gut microbes can affect TMAO levels through the fermentation of choline or L-carnitine to the intermediate compound trimethylamine (TMA), followed by oxidization of TMA by flavin monooxygenases to TMAO in the liver. 167 The addition of TMAO to an infant mouse model of V. cholerae infection promoted CT production during colonization, a process that accelerated in the presence of reactive oxygen species (Figure 4). 168 Since several commensal gut microbes have been implicated in the accumulation of TMAO, 169,170 the differential ability of different microbiomes to affect TMAO levels may thus be a metabolic factor in promoting or inhibiting V. cholerae pathogenesis.…”
Section: Gut Microbiomementioning
confidence: 99%